CircRIMKLB promotes myoblast proliferation and inhibits differentiation by sponging miR-29c to release KCNJ12 - Jian Wang; Yifan Wen; Jiawei Xu; Binglin Yue; Jialin Zhong; Li Zheng; Chuzhao Lei; Hong Chen; Yongzhen Huang (Epigenetics, 2022)
Muscle development is a complex process that was regulated by many factors, among which non-coding RNAs (ncRNAs) play a vital role in regulating multiple life activities of muscle cells. Circular RNA (circRNA), a type of non-coding RNA with closed-loop structure, has been reported to affect multiple life processes. However, the roles of circRNAs on muscle development have not been fully elucidated. The present study aimed to determine whether and how circRIMKLB affects muscle development. Our study revealed that circRIMKLB promoted myoblast proliferation and inhibited differentiation. Besides, miR-29c was proved as a downstream target of circRIMKLB using dual-luciferase reporter assay and RNA-binding protein immunoprecipitation (RIP) assay. Also, potassium inwardly rectifying channel subfamily J member 12 (KCNJ12) was identified as a novel target of miR-29c via dual-luciferase reporter assay, quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR), and western blot. CircRIMKLB and KCNJ12 were both proved to regulate cell cycle on muscle regeneration after injury in vivo. In conclusion, we demonstrated that circRIMKLB sponged miR-29c, releasing KCNJ12 to regulate myoblast proliferation and differentiation and regulating cell cycle during muscle regeneration after injury in vivo.